2010
DOI: 10.1111/j.1600-0846.2010.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Colour change in the human histamine wheal made visible by LYYN: a technique to enhance colour differences

Abstract: The LYYN technique was sensitive enough to discover a rapid colour change in the histamine wheal, a change that has not been described before.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
0
8
2
Order By: Relevance
“…During a wheal reaction it has been shown that clinical photography with enhanced colour differences is more sensitive in detecting differences compared to ordinary photographs using colour quantification software. A peak in red colour is found after 8 minutes followed by a rapid decrease in red colour . Compared to our data in which the superficial vessels at 150 and 300 μm show a rapid increase in blood flow from baseline to 8 minutes, it may be implied, that the flare of histamine induced wheals reaches peak value after ≈8 minutes.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…During a wheal reaction it has been shown that clinical photography with enhanced colour differences is more sensitive in detecting differences compared to ordinary photographs using colour quantification software. A peak in red colour is found after 8 minutes followed by a rapid decrease in red colour . Compared to our data in which the superficial vessels at 150 and 300 μm show a rapid increase in blood flow from baseline to 8 minutes, it may be implied, that the flare of histamine induced wheals reaches peak value after ≈8 minutes.…”
Section: Discussioncontrasting
confidence: 74%
“…A peak in red colour is found after 8 minutes followed by a rapid decrease in red colour. 24 Compared to our data in which the superficial vessels at 150 and 300 μm show a rapid increase in blood flow from baseline to 8 minutes, it may be implied, that the flare of histamine induced wheals reaches peak value after ≈8 minutes. The broadest field of view for investigating inflammation can be achieved by thermography.…”
Section: Quantification Of Wheal Reactions and Cutaneous Blood Flowcontrasting
confidence: 83%
“…In ophthalmology, digital photography and analysis are used for diagnosis of the anterior eye segment [37], for vessel detection in corneal transplants [38], for analyzing the corneal involvement of pterygium conjunctivae [39,40], for noninvasive calculation of hemoglobin in the wide field of emergency medicine [41], for examining rotational stability of intraocular lenses [42], in diagnosis of dry eye [43] and in the observation of side effects of antiglaucomatous treatment [44]. In dermatology they are implemented for measuring erythema and edema of the skin prick test [45,46,47] or intradermal skin tests [48], for analyzing repigmentation during treatment of vitiligo [49], for quantification of skin lesions [50], and in diagnosis and treatment of atopic dermatitis [51,52]. Otorhinolaryngology makes use of this technique during endoscopic transsphenoidal pituitary surgery [53] and for video-laryngoscopic-assisted surgery [54], while it is used for analysis of body posture in patients with asthma [55,56] in pediatrics.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of medical students who were skin prick tested with histamine, we detected a colour shift of the wheals from pale red to darker red between the 18th and the 20th minutes after the skin prick test (SPT) . One suggestion to explain the colour shift found was total desensitization of histamine H1 receptors (H1 receptors) in turn causing change of post‐capillary resistance vessels from vasoconstriction to vasodilatation.…”
Section: Introductionmentioning
confidence: 99%